Gastrointestinal Adverse Events Observed After Chimeric Antigen Receptor T-Cell Therapy. (October 2019) - Abu-Sbeih, Hamzah; Tang, Tenglong; Ali, Faisal S.; Luo, Wenyi; Neelapu, Sattva S.; Westin, Jason R.; Okhuysen, Pablo C.; Foo, Wai Chin; Curry, Jonathan L.; Richards, David M.; Ge, Phillip S.; Wang, Yinghong
Abstract : Background: Chimeric antigen receptor T-cell (CART) therapy can significantly improve outcomes for patients with certain hematologic malignancies. The most notable drawbacks of CART are cytokine release syndrome and CART-related encephalopathy syndrome. Gastrointestinal adverse events (GI-AEs) have not yet been reported in association with CART. Herein, we describe the incidence and clinical features of GI-AEs observed after CART. Materials and Methods: We report a case series of patients with hematologic malignancies who received CART, in a clinical trial or as the standard of care, and subsequently suffered from GI-AEs between 2012 and 2018. Results: In our cohort, 37 of 132 (28%) patients experienced GI-AEs. All 37 experienced diarrhea with a median onset of 7 days (interquartile range, 4 to 25 d) after CART infusion. The median age of these patients was 58 years. Most had diffuse large B-cell lymphoma (51%). Seventeen patients experienced cytokine release syndrome, and 9 experienced CART-related encephalopathy syndrome. The interleukin-6 antagonist was required in 15 patients. Overall, 49% of patients had grade 1 diarrhea, 32% had grade 2, and 15% had grade 3. Other gastrointestinal symptoms in these patients were abdominal pain (41%), nausea and vomiting (49%), fever (8%), bloody stools (3%), and abdominal distension (5%). The median duration of symptoms was 6 days (interquartile range, 3 to 9 d). In 32 patients who underwent imaging, 8 (25%) had findings suggestive of gastrointestinal tract inflammation. Nine (24%) patients experienced GI-AE recurrence after initial improvement. The symptoms were attributed to an alternative cause in 17 (13%) cases and to CART in 20 (15%) cases. One patient developed CART-related refractory colitis that eventually responded to antibiotics for pneumonia. Conclusion: CART-related GI-AEs occur in 15% of patients treated with CART. These symptoms are typically mild and self-limiting, requiring only symptomatic treatment. Nevertheless, CART may, in rare cases, lead to refractory colitis.